2017
DOI: 10.1136/bcr-2016-219121
|View full text |Cite
|
Sign up to set email alerts
|

Levetiracetam-induced eosinophilic pneumonia

Abstract: Levetiracetam is widely regarded as a benign antiepileptic drug, compared to older antiepileptic medication. We report a case of eosinophilic pneumonia due to levetiracetam use in a non-smoking woman aged 59 years with no previous respiratory history. Our patient presented with exertional breathlessness and marked desaturation on exertion. She displayed 'reverse bat-wing' infiltrates on her chest radiograph and peripheral eosinophilia on a complete blood count. Her symptoms, radiology and peripheral eosinophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In our study, been reported in some patients receiving LEV therapy, there is no study reporting on the occurrence of pancytopenia during the long-term follow-up of the patients (11). Moreover, although LEVinduced eosinophilic pneumonia and B cell aplasia have been reported, there have been no reports of LEV-induced monocytic change (12,13). Our findings indicated that the patients had no anemia and had increased Hgb and Htc levels at three years of LEV therapy; however, their MPV and WBC levels showed no significant difference, which could be associated with the hemoconcentration induced by LEV.…”
Section: Discussionmentioning
confidence: 54%
“…In our study, been reported in some patients receiving LEV therapy, there is no study reporting on the occurrence of pancytopenia during the long-term follow-up of the patients (11). Moreover, although LEVinduced eosinophilic pneumonia and B cell aplasia have been reported, there have been no reports of LEV-induced monocytic change (12,13). Our findings indicated that the patients had no anemia and had increased Hgb and Htc levels at three years of LEV therapy; however, their MPV and WBC levels showed no significant difference, which could be associated with the hemoconcentration induced by LEV.…”
Section: Discussionmentioning
confidence: 54%
“…It is a unique AED that has multiple mechanism of action that differentiates it from conventional AEDs. But in recent years, apart from the most frequent adverse effects of LEV, such as nausea, gastrointestinal symptoms, dizziness, irritability and aggressive behavior, some rare adverse effects of LEV have been reported, including eosinophilic pneumonia, rhabdomyolysis, thrombocytopenia, elevated kinase and reduced sperm quality [17–19] . However, evidence for a relationship between LEV serum concentrations and risk of adverse effects remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…But in recent years, apart from the most frequent adverse effects of LEV, such as nausea, gastrointestinal symptoms, dizziness, irritability and aggressive behavior, some rare adverse effects of LEV have been reported, including eosinophilic pneumonia, rhabdomyolysis, thrombocytopenia, elevated kinase and reduced sperm quality. [17][18][19] However, evidence for a relationship between LEV serum concentrations and risk of adverse effects remains unclear. Further larger, prospective studies will be required to investigate the safety of LEV in the treatment of pediatric epilepsy…”
Section: Discussionmentioning
confidence: 99%
“…We report a case of adult-onset LEV-induced ILD. Only one reported case of lung injury caused by LEV in an adult was found via a PubMed search [ 10 ]. This previous case was diagnosed as eosinophilic pneumonia based on non-segmental infiltrates detected by CT and findings of increased peripheral eosinophils.…”
Section: Discussionmentioning
confidence: 99%